A AN EVALUATION OF GENOCIDE-THE GENOCIDE CRIME - Karo, Emina (International Scientific Journal Vision, 2017)
Genocide crime was through the history of humanity. Genocide crime is known as a crime of crimes,and internationally wrongful act. Because crime’s intent is to destroy group of people in whole or in part. Unfortunately, this crime is continuing with increasing and becomes one of the main crimes of nowadays. Therefore there is a constant need to deal with this crime. This crime needs to be seen as a big problem in the world and to be taken as a interdisciplinary crime. It is obligation for international community, international organizations and law to take more active role in this field as well. This crime has a specific challenges for a convintion. Genocide Convention should be more wide-reaching, especially about some crimes, commited to acultural and social groups. State responsability for genocide must be involved in national legislations, without exceptions.This study provides reflections on Genocide Convention adopted in 1948, the genocide trials and implementations, punishing genocidaries, evaluating the genocidial situation.